PERLINDUNGAN HUKUM TERHADAP LAHAN PERKEBUNAN DAN PERTANIAN MASYARARAKAT AKIBAT TERJADINYA ALIH FUNGSI LAHAN - Permai Yudi; Lyndon Parulian Nainggolan; Bobby Sutra Saragih (Universitas Quality, 2021)
Handling the problem of land transfer in Indonesia into plantation and agricultural landis increasingly happening, especially forest land and / or former plantation land managedby the State. The province of North Sumatra is one of the areas that has many areas thathave a transition of land functions into plantation land and / or agricultural land ownedby the community, so it needs attention by the central government and local governmentin providing legal certainty and protection to the community. Endorsement or recognitionof land that is transferred to plantations and or agriculture must get special attentionfrom local governments, especially the central government, so that the transition of theuse of land that was once forest land and or plantation land is clearly allotment. The purpose of this research is to find out the legal arrangements on legal protection ofplantation land and / or agricultural land owned by the community, and to know theallocation of land in its use by the community both in the field of plantations and / oragriculture so that it can be said productive land. The research method used today is thelibrary review approach, by describing in writing form, in relation to laws andregulations related to forests and plantations and agriculture. The targeted external isoutside the mandatory Journal of Justiqa published by the Faculty of Law, University ofQuality.